(untitled) - YANI AZMI, AHMAD (Language Horizon: Journal of Language Studies, 2014)
Edward Cullen’s Masculinity in Stephenie Meyer’s New Moon Ahmad Yani Azmi English Literature Faculty of Languages and Arts State University of Surabaya Ahmadyanianjemi007@gmail.com Dr.Ali Mustofa, M.Pd. English Department Faculty of Languages and Arts State University of Surabaya Abstrak Tesis ini bertujuan untuk mengetahui maskulinitas dalam karakter utama dari Stephenie Meyer New Moon , Edward Cullen . Hal pertama yang dibahas adalah keprihatinan masalah dalam karakteristik maskulinitas ditemukan dalam Edward Cullen . Edward Cullen hidup dalam keluarga di tengah-tengah masa perang dan terdidik oleh keluarga yang baik . Latar belakang pendidikan yang diperoleh dari keluarganya membuat Edward Cullen menjadi manusia maskulin yang dominan , berani, cerdas , rasional , analitis , agresif , dan mandiri . Kemaskulinan Edward ini kemudian menjadi dasar dalam kehidupan sosialnya . Kedua, membahas keprihatinan masalah dalam dampak maskulinitas Edward Cullen dalam hidupnya . Kemaskulinan Edward Cullen memberi dampak dalam hidupnya dengan membuatnya menjadi manusia individu dengan sifat karismatik yang kuat . Karakter individu yang kuat mendorongnya menjadi pintar untuk memberikan alasan yang baik dalam setiap keputusan yang dia ambil. Kekarismatikan Edward Cullen dapat dilihat dari keputusan bijaksana yang ia ambil dan penampilannya yang tampan dan menawan. Konsep peran jender dari Sigmund Freud digunakan untuk mengungkapkan tentang karakter maskulinitas Edward Cullen . Selain itu , tujuh karakteristik utama maskulinitas oleh Macionis digunakan untuk mengungkapkan lebih dalam karakter maskulinitas Edward Cullen . Novel New Moon sebagai data utama akan disertai dengan data tambahan untuk menjelaskan secara mendalam dari penerapan teori . Hasilnya akan menunjukkan bahwa Edward Cullen adalah manusia maskulin yang memiliki karakter maskulin seperti ditemukan dalam teori yang digunakan . Kata kunci : rasionalitas , cerdas, keberanian , kemandirian , analitis , dominasi , agresivitas . Abstract This thesis intends to reveal the masculinity in the main character of Stephenie Meyer’s New Moon, Edward Cullen. First discussed problem concern in masculinity characteristics found in Edward Cullen. Edward Cullen that is live in family in the middle of the war is educated by well family role. His educational background by his family make Edward Cullen become masculine man that is dominant, brave, intelligent, rational, analytical, aggressive, and independent. Then his masculinity becomes his base in his social life. The second discussed problem concern in the impact of Edward Cullen’s masculinity in his life. Edward Cullen’s masculinity impact his life by make him become strong individual and charismatic man. His strong individual character pushed him become smart in order to give good reason in every decision he took. Edward Cullen is charismatic man because he is wise in every decision he took and his personality appearance that is good looking and charming. The concept of gender role from Sigmund Freud is used to disclose about Edward Cullen’s masculinity character. In addition to that, seven main characteristic of masculinity by Macionis are used to reveal deeper to Edward Cullen’s masculinity characters. The novel New Moon as the main data will be accompanied by the additional data in order to elaborate deeply from the application of the theory. The result will shown that Edward Cullen is masculine man that is has masculine characters as be found in the theory which is used. Keywords: rationality, intelligent, bravery, independence, analytical, dominance, aggressiveness. INTRODUCTION Novel is one kind of fiction that is created by human. Fiction is not reflected and understood easily. Novel provides some complex ideas that support reader’s thought. For one thing, novel gives a deeper and better acknowledge about human life for it has an ability in showing human affairs in depth and fully. The second reason is that “novels are long words with great amount of details in every page” (Peck, 1988:103). Detail is not created to make the reader confused but it helps to recognized how complicate the reality is the character has to face. Thus far, it is important to take details into account before the reader makes any kinds of judgments for they present all complicating facts (Peck, 1988:103). Complication and details in novel have also aroused the interest to write the thesis analyzing novel. The last reason is relative to the function of novel, which is to give enjoyment and understanding to the readers. This idea is in accordance with Perrine’s, that to have a convincing claim on our attention fiction must yield not only enjoyment but also understanding (1959:3). Besides those, Lukacs sees the emergence of novel as the major modern genre is in as the result of a change in the structure of human consciousness; the development of the novel reflects modification in man’s way of defining himself in relation to all categories of existence (Bernstein, 1984:14). He also defines novel as dialectic of form-giving and dialectic of interpretation and representation (Bernstein, 1984:18). Fiction has close relation to men and masculinity. The idea of fiction secretly depicted unusual phenomenon that happen in world that is set to be real. The understanding of masculinity is simultaneously broad and narrow in scope. According to Burrm (2002), “broad and scope because we are dealing at once with a characterization of masculinity that must obtain over a population and narrow because any conception must be specific to each individual within that population”. Putting it into other simpler words, masculinity is a concept of being a man, owned by each male but besides by his own self, it is very much affected by the perspective and beliefs of the society. Thus, the definition of masculinity above is to make clear that in order to have a good understanding or to do an analysis of masculinity, it cannot be treated as something completely general. Man with tremendous character often compared to the women who have always considered weaker. But not all men possess the nature of masculinity which is recognized as the nature of men. Not the least of men with male gender but does not have a masculine nature. In masculinities R.W. Connell notes that “Masculinity is not an idea in the head, or a personal identity. It is also extended in the world, merged in organized social relation” (1995:29). Social environment may be forming nature of man that is growing, or to establish the nature of masculinity. Fully educated man by a woman without knowing a father can make a man with a gentle nature like a woman or it could also make men lose their natural masculine and become feminine, or could be called feminine-male. Early thinking often assumed that this division is based on underlying innate differences in traits, characteristics and temperaments of males and females. In the other context, measure of femininity or masculinity was often used to diagnose what were understood as problems of basic gender identification, for example, feminine-males or masculine-females (Burke and Stets, 1980:998). Actually masculinity doesn’t always exist in male body, but there is also possibility that masculinity can also appear in female body (Halberstam, 1998:16). In Encyclopedia of Sex and Gender, Freud concludes that each individual is psychologically bisexual: Masculine and feminine traits exist in everyone. In addition to resisting a unitary construction of masculinity, Freud’s position on bisexuality firmly divides biology from gender. The feminine man and the masculine woman become combinations of biology and gender that are not possible but are likely (2007:969). Story about men who is ’different’ is not just fiction in novels or another written story. Their existence that are ’different’ appears in the story came from real life that is really happening around us in this era. Now is the time where men asked about cosmetics, and women began to love football. This behavior does not seem normal shortly. But as said above, that is not as easy as it determines men are not masculine, or women not feminine based on what they do. Men still considered masculine even though they asked about cosmetics and start to wear cosmetics. Women also still be feminine even though they started liking football which is synonymous with the activities of men. This statement confirms that what someone does not merely explain his/her personality. Topic of masculine and feminine are still ambiguous around us is interesting for a deepened understanding. This thesis focuses deeper understanding of the nature of masculine men. Men are identical with the leaders and rulers were often highlighted its existence. Masculine itself is a natural thing that should be owned by men, although men are men discussed a ’different’. Men still have a distinct masculine traits compared with women who have the possibility to have a masculine nature. Stephenie Meyer is an American talented writer who has written Twilight Saga novels. Stephenie Meyer has a special feature in every novel she wrote. Although each novel she writes emerge from different inspirations, his novels always have a special theme, the theme of heroic. The rescue action of the loved ones by the main character in the novel. Super hero in her novel both men and women, has a masculine feature that support their heroic actions. The twilight saga, clearly told Edward’s heroic action saves Bella; within the host, also told how Wanda rescue her loan body and last human family remains from the attack souls which wanted to dominate the earth. Masculinity perfectly blended in her novels. In addition to having a strong masculine themes that is arranged in each novel, the work of Stephenie Meyer has advantages that make this thesis chose one of her novels as the material. novel by Stephenie Meyer has always been a New York Times Best Seller List, and won the British Book Award. Her novels also became very well known, the series has sold over 100 million copies worldwide in 37 languages??. In 2008, the four books of the series Claimed the top four spots on USA Today’s year-end bestseller list, making Meyer the first author Stepehenie to ever Achieve this feat, as well as being the bestselling author of the year. The Twilight novels held the top four spots on USA Today’s year-end list again in 2009. The fame of novels by Stephenie Meyer, continues in its adoption into the movie. These films made ??the works of Stephenie Meyer’s increasingly popular, for those who have never read the novel. The success also achieved in every novel that was filmed. Differences in masculine theme in the novel Twilight Saga New Moon from other novel lies in the character of Edward addressing what is happening in his life. The peak where Edward feels really have to leave Bella, not because no longer loves Bella, but because he loves Bella too much. Edward is more concerned with Bella’s safety than his selfishness defend Bella. In the Twilight Saga other novels, Edward looks so masculine and willing to do anything for Bella. In the Twilight novel, Edward saves Bella from nomadic vampires, James, and suck Bella’s blood from James’s toxins so Bella did not turn into a vampire. In Eclipse, the third sequel in the Twilight Saga, Edward and his family are willing to fight against the new born vampires to save Bella from revengeful of Victoria, James’s spouse. And in the last sequel from Twilight Saga, Breaking Dawn, Edward fought the Volturi to protect his family. In these novels clearly told that Edward was so brave to defend his family, the people he loves, Edward was willing to do anything, survive and retain the beloved ones. While in New Moon, Edward seems leave Bella so easy, left her without protection and do not seem willing to love Bella anymore. Look different attitude taken, but this difference is not a reason in determining the nature of masculine Edward. Stephenie Meyer’s New Moon is the second sequel of Twilight saga. As the information above about Edward’s different attitude in the New Moon, makes this sequel is interesting to be studied. All the novels by Stephenie Meyer are full of masculinity theme, but the theme of masculinity in New moon different from her other novels. The title of New Moon refers to the darkest phase of the lunar cycle, indicating that New Moon is about the darkest time of protagonist Bella Swan’s life due to Edward’s masculinity features. This novel tells Bella’s story of the lost love of her life since Edward left her. Edward is masculine character who became the main character in the novel twilight saga, disappeared in order to save Bella. Edward’s masculine attitude made him look not masculine. But based on the previous statement, that the determination of one’s masculinity is not merely determined by their behavior, because surely there is a reason behind everything he does. Edward has different masculinity in this novel. According to the brief story in background of the study that gives explaination of masculinity in the novel, it appears two questions as the problems: 1. What are masculinity features found in Edward Cullen character in Stephenie Meyer’s New Moon? 2. What is the impact of Edward Cullen’s masculinity on his life in Stephenie Meyer’s New Moon? METHOD In order to give factual explanation on the subject mentioned on the previous chapter, this chapter would deliberately mention what are the related literatures that will be used to analyze the problems. These related literatures are the tools to analyze the subject matter later on the third chapter. MASCULINITY The Definition of Masculinity Masculinity as a word, as it is defined in Oxford Advanced Learner’s Dictionary (1995), is the quality of being masculine, whereas the term masculine is defined as “having the qualities or appearance consider to be typical of or appropriate for men” (Oxford Advanced Learner’s Dictionary, 1995). In general, masculine is something that is related to Virility of men. but masculine and men are not forever united. Masculine is a feature, while the male is gender. Because masculine is feature of the human, masculine feature may arise in men and women. Meanwhile, in masculinities R.W. Connell notes that “Masculinity is not an idea in the head, or a personal identity. It is also extended in the world, merged in organized social relation” (1995:29). According to Terman and Miles , in western culture, stereotypically, men are active, competent, rational, independent and adventurous; while women are passive, less competent, irrational, dependent and unadventurous. Early thinking often assumed that this division is based on underlying innate differences in traits, characteristics and temperaments of males and females. In the other context, measure of femininity or masculinity were often used to diagnose what were understood as problems of basic gender identification, for example, feminine-males or masculine-females (Burke and Stets, 1980:998). Furthermore, Halberstam argues that there is a possibility that masculinity can also appear in female body (1998:16). The possibility of masculinity and femininity that could be mixed together is strengthened by Freud argument in Encyclopedia of Sex and Gender, Freud concludes that each individual is psychologically bisexual: masculine and feminine traits exist in everyone. In addition to resisting a unitary construction of masculinity, Freud’s position on bisexuality firmly divides biology from gender. The feminine man and the masculine woman become combinations of biology and gender that are not only possible but are likely. (2007:969). It is known that femininity and masculinity are not innate but are based upon social and cultural conditions. Characteristics of masculinity according to Andler, it can be described as a strong individual figure, firm, brave, and similarity. Individual who has a masculine gender have an independent nature, steadfast, strong spirit of curiosity, self confidence and courage to take a risk (1993:48). GENDER In Encyclopedia of Sex and Gender, Judith Roof defines gender as a condition of being female or male, but also includes the behavioral, cultural, or psychological traits typically associated with one sex into its meaning. Furthermore, gender may additionally refer to an individuals sexual identity, especially in relation to society or culture (2007:628). According to Jolly, Gender is different with sex. She argues that gender refers to the array of socially constructed roles and relationships, personality traits, attitude, behaviors, values, relative power and influence that society ascribes to the two sexes on a differential basis. Whereas biological sex is determined by genetic and anatomical characteristics, gender is an acquired identity that is learned, changes over time, and varied widely within and across cultures. Gender is relational and refers not simply to women or men but to the relationship between them (2006:3). GENDER STEREOTYPES Parke argues that a gender stereotype is a predetermined set of attitudes and behaviors that is believed to be typical of all men or women. Stereotypes about gender assume that there are in fact only two gender: male and female (2007:622). This definition also strengthened by Linda’s argument that defines a gender stereotype as beliefs about the psychological traits and characteristics as well as the activities about masculinity and femininity (1976:168). According to Parke, this idea of opposites has resulted in gender stereotypes that are an exaggeration of the real physical, social, and psychological differences between the sexes. Feminine traits include being emotional, submissive, weak, cooperative artistic, and home-focused; masculine traits include being rational, unemotional, aggressive, competitive, strong, scientifically, of mathematically skilled, and career-focused. In many cultures masculine traits traditionally have been valued as superior to feminine ones (2007:622). GENDER ROLES According to Roof, gender roles are sets of culturally defined behaviors such as masculinity and femininity. In most cultures this binary division of gender is roughly associated with biological sex-male or female. There is much variation within the categories of the masculine and the feminine, both in terms of the possible presentation of gender and the tasks deemed appropriate to each gender. There is also great variation in the degree of relation between gender and sex within and among cultures. Some cultures understand gender as only loosely linked to biology and assume gender is an effect of and flows naturally from biological sex (2007:616-617). Robert Brannon argues that the male gender role or female gender role is like a script that men and women follow to fulfill their appropriate parts in acting masculine or feminine (Linda, 1976:168). He adds, the best way to understand gender is to understand it as a process of social presentation. Because gender roles are delineated by behavioral expectation and norms, once individuals know those expectation and norms, the individual can adopt behaviors that project the gender he/she wishes to portray (Linda, 1976:169) John Money invents the term gender roles to mark a distinction between behaviors related to one’s biological sex and those related to social practices and individual gender identity. The notion that masculine roles and feminine roles, while related to biological sex, are not determined by differences in male and female genitalia had a significant impact both on the historical interpretation of social orderings and on understandings of traditional gender roles (2007:618). TRADITIONAL GENDER ROLE Traditional gender roles cast men as rational, strong, protective, and decisive; they cast women as emotional (irrational), weak, nurturing, and submissive. These gender roles have been used very successfully to justify inequities, which still occur today, such as excluding women from equal access to leadership and decision-making positions (in the family as well as in politics, academia, and the corporate world), paying men higher wages than women that they are not fit for careers in such areas as mathematics and engineering (Tyson, 2006:85). Kristina Quynn explains that traditional gender roles furthermore appear the structural binarism of gender roles producing an artificial opposition in the qualities imagined to belong to each gender. If males are smart, females must be less smart. If males are strong, females are weak. This binary system sustains the oppression of women as an inferior class of beings and keeps most people from realizing their full feminist have observed, to justify and maintain the male monopoly of positions of economic, political, and social power. Traditional gender roles have a great deal with patriarchy system that continually exerts forces undermining women’s self-confidence and assertiveness, then points to the absence of these qualities as proof that women are naturally, and therefore correctly, self-effacing and submissive (Tyson, 2006:86-87). GENDER IDENTITY Jaime Hovey defines gender identity as the differing cultural and social roles that men and women inhabit, as well as the ways in which individuals experience those roles, both internally and in terms of the ways they present themselves to the world through their manner of dress, behavior, physical comportment, and so forth. Both distinguish between a person’s biological sex (male or female) and gender identity (masculine or feminine) (2007:614). Furthermore, Schaefer defines gender identity as the self-concept of a person as being male or female. Gender identity is one of the first and most far-reaching identities that human being learns (1992:325). From sociological perspective, gender identity involves all the meanings that are applied to oneself on the basis of one’s gender identification. In turn, these self-meaning are a source of motivation for gender-related behavior (Burke and Stats, 1980:996). A person with a more masculine identity should act more masculine, that is, engage in behaviors whose meanings are more masculine such as behaving in a more dominant, competitive and autonomous manner. It is not the behaviors themselves that are important, but the meaning by those behaviors. SEVEN MAIN CHARACTERISTIC OF MASCULINITY ACCORDING TO MACIONIS Dominant. Dominance means that the disposition of an individual to assert control that can influence other’s action (Cambridge, Third edition). People with dominant characteristic also have a great power or authority to support them (Lehman, 2001:11). They try to dominate in all activities and behave as if they are best judge. They always want each word they say not to be argued. Brave. Bravery is the ability to confront fear, pain, risk/danger, uncertainty or intimidation (Cambridge, third edition). It also can be defined as the ability to control fear from danger, illness, and the uncomforted circumstances and feelings (Oxford, Third edition). According to Lehman, a brave person doesn’t always free from fear, but they can suppress the fear until they can handle and control the dear, not as the contrary, fear controls them (2001:10). Rational. Being rational can be defined as the ability for showing reason than emotion (Oxford, third edition). According to Connell, rational people are someone who can see a problem logically. He adds, they will make a strong effort to determine all the significant fact necessary to make a particular decision before that decision is made into reality. They also have capability for considering the bad effects and the good effects before deciding a decision (1995:46). Intelligent. Intelligence is the ability to reason, plan, solve problem, think abstractly, comprehend complex ideas, learn quickly and learn from experience (Cambridge, third edition). It is not merely book learning, a narrow academic skill, or test-taking smarts. Rather, it reflects a broader and deeper capability for comprehending the surrounding (Lehman, 2001:19). In short, being intelligent is being clever. Analytical. Being analytical is having ability in solving problem based on good analysis (Connell, 1995:39). He adds, analytical people usually see a problem from various perspectives (1995:40). In addition, according to Lehman, they also examine the problem closely and thoroughly (2001:15). The analysis is also equipped by several data and factual information. So, the result of analysis is credible and accountable. Aggressive. Being aggressive is characterized by making an all-out effort to win or succeed (Oxford, Third edition). According to Connell, aggressive people usually behave in very forceful and determined way in order to succeed. They are also characterized by being assertive, bold and energetic. Furthermore, the are brave to take a high risk to realize their ambition (1995:32). Independent. Being independent is having ability to not rely other in support, care or fund (Cambridge, Third edition). Connell argues that independent people have freedom of dependence and exemption from reliance. EDWARD CULLEN MASCULINITY FEATURES Edward Cullen masculinity features are really influenced by his family background. The way he was born in a family in the middle of the war, formed him into a masculine character of man. Characteristic of men who have to go to war and women who should be at home, taking care of family, made Edward has strong masculine features. His father was involved in the war at that time and his mother was a housewife. Gender roles in Edward’s family gave him big influence to Edward characteristic. This condition bring Edward planned to enter the military at the age of 18. Edward’s decision to joined military showed that he would take risk to prosperous his family and country. Edward hard determination to join in the war is not only a necessity but also to convey that he took the decision to protect his family, to bring peace to his family and his country. Edward’s protective feature proof that he would take all risk that might happen. His protective feature made him would be self-sacrifice for the salvation of a loved one. This family background had formed Edward so that he prefer save Bella with leave Bella alone. In short, Edward seemed to act out of selfness to save the one he loved. Edward’s mother who was at that time perceived as more morally upright than men. considered to be the backbone of familial morals, and added to this was the belief that females were more religious than males. This is largely because women composed the greatest number of church attendants, although men dominated the roles of religious leaders. Woman who is also a housewife taking care of children at home have a big role in the formation of her child character. Edward’s mother strong religious background made Edward perfect educated in religious knowledge and this makes Edward has more intelligence in response to religious issues. This can be seen from the conversation of Bella and Carlisle about Edward’s opinion in turning Bella into a vampire like him. There anything might still be life after death for creature like him is his worried about the choice to change Bella into a vampire. Edward analyzed so deeply that finding the answer of his existence, which makes him reluctant to change Bella and experienced bad thing according to him, losing soul. By the time his family had formed him, Edward grew up in different way. His fate become a vampire, saved him from Spanish Influenza that was epidemic in his place. Edward has grown with some character of masculinity that based on how his family has formed him first. According to Andler one of masculinity characteristic is strong individual figure that is make someone has an independent nature (1993:48). Edward has independent nature which make him has individual figure that as result of wartime education by his family. The phenomenon of his family background affects Edward’s characteristic, how he faces his life. He was not hurried find a mate. Edward masculinity characteristics of man are dominant, brave, rational, intelligent, analytical, aggressive and independent. Edward’s dominant feature showed when he decided to end his relationship with Bella unilaterally. Another feature of Edward masculinity is brave. According to Lehman, brave person doesn’t always free from fear, but they can suppress the fear until they can handle and control the fear, not as the contrary, fear controls them (2001:10), Edward did so. Edward took actions that prove he has controlled fear around him. Edward’s bravery had appeared in his defense of Bella in front of the Volturi when he wanted to cancel his request to die because he thought Bella had died falling off a cliff. Become rational has become the absolute masculinity feature qualities that should be have by men. Where they are taught to be have the ability to show what the reason than using their emotion. As stated by Connell that a rational person is one who can look at the problem logically. He also added that they will make a strong effort to determine all the significant fact necessary to make a particular decision before the dicision is made into reality. They are also able to see the good and bad effects before making a decision. (1995:46). Man rationality commonly influenced by brain that is thinking about reason and affect logically. Edward rational feature often seem appear in the novel,the moment when Edward will not let Bella bear the danger he caused in another day. Edward has stated that he won’t to live without Bella. Due to this, Edward’s rational trait is appear. Edward planed to provoke the Volturi to kill him if something happens to Bella that because of his actions. Live more than a hundred years make Edward Cullen has a very long time for get an education both formal and non-formal. Edward has made ??it beyond the human experience of human life in general. Twice graduated from medical school and several other education is his educational background. Edward Cullen also told to have the ability to read the minds of everyone around him and that was a few miles from him except Bella. Based on his educational background, Edward has intelligent character that is being able to make reason, plan, solve problem, understanding complex ideas, and learn from experience. According to Lehman intelligent is not just about book learning, a narrow academic skill, or test-taking smarts. (2001:19). In short, being intelligent is being clever. Edward can be identified as an analytical man. It is also possibly to be proved when he was watching Romeo and Juliet movie and knew how easy human to die. Edward was envy to Romeo who is easy to die rather than him. For him as a vampire who has marble skin that is so hard and unbreakable, death is something that seems impossible. Based on the whole story of Twilight Saga, Edward becomes very ambitious to Bella. Since the first, Edward is so ambitious to own Bella, both her blood and her body. Bella’s smell was different and Edward instinct of vampire wanted to taste it, but Cullens role that would never drink human blood limited Edward and make his feeling to Bella become ambitious in attention to keep her safe. Edward want to make Bella safe from everything, from his self also. According to Connell (1995:32) who is said that aggressive people usually forceful behave and determined way in order to succeed. Aggressive people are also characterized by being assertive, bold and energetic. Furthermore, they are brave to take risk to realize their ambition. Aggressive people that described have ambition to be reached, and Edward ambition is keeping Bella safe. Edward succeeds to make Bella save by force himself keep in control in physic relationship with Bella. Bella’s humanity is Edward reason to force himself in order to save Bella. Bella’s human body is so weak compare to vampire body. Edward aggressive characteristic can be identified when Edward and Bella launch their sexual aggression. Although they were in love each other, but Edward stayed in control in showing his aggression to Bella. Refers to the meaning of independent itself that is not dependent to others, do not need others support and do not controlled by others, it can be determined that Edward have a dominant independent feature. Which can be seen in the novel, Edward depend on the existence of Bella in this world indeed, but he had controlled himself not to have to make Bella always by his side. The existence of Bella is more than enough; at least he got Bella still alive, still human. Either that Bella was on his side or not, but the existence of Bella in this world is the most important to him, and greatly affect to his life and death. Edward has joined into social life using his characteristic and based on gender identity. According to the theory of gender identity, Jaime Hovey stated that defines gender identity as cultural and social roles differences of men and women a place to stay. How to dress and behave is a way to distinguish between masculine and feminine in gender identity theory (2007:614). Edward has such as a prince charming characteristics that clearly proves that Edward is a masculine figure. He retains some of traditional mindset and dated patterns of speech. Edward Cullen’s latest mindset proves that true love still exists. Girl’s obsession about prince charming is undeniable and Edward has prince charming features that are imagined by every girl so it becomes Edward masculinity feature. Girls are not longer dreaming of the perfect man, they no longer dreamt of brave knights, rich lords, soldier of charismatic pop stars. Some people think the modern view of true love is deteriorated. However, modern romance has been morphed enough be our culture that Edward Cullen could be declares the next prince charming. Like the traditional prince charming, Edward does have super-human strength, is physically attractive, and defends his woman when necessary. Another reason why Edward latest mindset is prove that true love still exist is that he denies part of himself to be with Bella. Many girls dream of having this affect on today’s men, who are so often non-committal and emotionally turbulent. Most girls consistently find themselves ignoring the warnings of friends and believing that a man will change for the right girl, and they obviously think the right girl is always themselves. Girls want to believe that they can be the inspiration for man’s change toward becoming a committed, loving, and unashamed companion. Edward Cullen as prince charming may be ‘step down’ in the history of princes but he is reality of our changing world. Girls will take the moral ambiguity and mysteriousness of men like Edward with the hope that they will be transformed by love to become faithful, loving men. Love’s first kiss is no longer coming from a prince on a white horse, but instead from a man that lives in the shadow: a man who may or may not deny the dark secret of inadequacy, sinfulness, and emotional struggle. Edward character looks ancient when should be compared to the male characters in general now. This can be seen from the way he treats Bella. Bella’s self argues that Edward is old schooltype. Premarital sex is not Edward’s seeking election. Edward chose to marry Bella first before deciding to have sex with her. Responsibilities and capabilities such as a masculine man. THE IMPACT OF EDWARD CULLEN’S MASCULINITY IN HIS LIFE Possessed nature and character always have an impact on someone individual’s own life. Good and bad effects will always appear accompany the selected action. Edward Cullen as the main character in the New Moon novel which clearly have a masculine features in his life. Masculinity features of Edward Cullen influence in his life, made ??him get good and bad effects of any actions taken based on the features he owns. The affect of Edward Cullen’s masculinity his life is being strong individual and charismatic man. His strong individual made him become a strong person and dominant. With his entire masculinity feature Edward Cullen become a charismatic man who has good looks and behaves. Edward Cullen’s strong individual is the impact of his masculinity feature. His individual feature allows him to be a strong person to stand alone and have complete control over his life. Edward Cullen is able to take a final decision on his own without the other influence him, even someone he loved the most. Edward Cullen decides to leave Bella, though Bella had begged him to stay and his family reminds him that Edward and Bella are dependent on each other. But Edward still on his decision and implementing actions from what he has taken into consideration. In addition to the moment when Edward left Bella, Edward was also a strong individual when he was apart with Bella. Edward stay away from the people living around him. Edward went away from Bella, also from his family, trying to stand without relying on anyone. Edward makes him capable; did not bother anyone else in the situation that is actually broke his heart. Edward dominant feature impacts on the pain caused by a unilateral decision that he took by himself, which leaves Bella. Edward pushed his opinion about life to Bella, where he take dominant posisition in arguing with Bella. Even Bella begged him not to leave, he pushed his opinion which he tought the best for their relationship. His dominant character leads him become brave in order to take responbility of his decision of his dominant character. His dominant character make Edward must have courage to bear the decisions he took. Edward survived bear the pain, forcing himself to be strong, for the safety of Bella. His dominant and brave feature has affect his life by make him suffer because of his own decision. Edward exceptional understanding of the life that he was facing very well because of intelligence and vast knowledge he has because his strong individual has been leading him. With the intelligence that he had, Edward being able to solve problems in his life. Edward be able to make excuses, find a way out of the problem and understand the complex understanding of life and existence, such as the definition of intelligence that uttered by Lehman (2001:19). Because of his intelligence, Edward was able to infer how his life without Bella. So he went to the Volturi decide to commit suicide as a solution to the problem. Edward has over-protective feature as the impact of his strong individual character. Edward should be forced to suffer by his own decision. Because of his strong individual character, Edward becomes overprotective to Bella. His strong understanding wont be defeated by anything, that’s why Edward pushed his opinion to himself that human soul is pure. Edward reluctantly had to leave Bella in order to save Bella. Edward is very protective on Bella’s soul, Edward really did not want Bella lost souls like him. Bella’s safety has become the most important thing in his life from the beginning he met Bella, so anything that might be dangerous for Bella would blocked by him as much as possible. Edward would act as much as possible to protect her even if it cost with his life forever. Beside of being protective, being dominant also make Edward become aggressive. As presented by Connell is being individuals who are willing to work hard to achieve success, it is clear already done Edward and prove that he successfully achieved what he wanted. Edward is able to control himself, though with very hard for reject Bella’s invitation. Edward goal is to keep Bella safe, and he struggled for the goal, and Edward was succeeded by his efforts. Edward Cullen’s masculinity affect him to be charismatic. Edward became a men with very masculine appearance and charming. Edward is a masculine individual based on how he looks and behaves. Edward also has good manners and polite in front of the people around him. This makes Edward liked people who are nearby. From the appearance of Edward, Bella is concluded that Edward is a masculine charming men. As explained earlier, that according to the theory of gender identity, masculine men has masculine well dressed, good manner and behavior. It can be proven through the description of Bella to Edward when Bella saw Edward in the first time. “The last was lanky, less bulky, with untidy, bronze-colored hair. He was more boyish than the others,” (2006:06). Bella described Edward as the most handsome men in the Cullens member. And Edward polite quote proofed by his manner ask Charlie to invite Bella come join the Cullen to Bella’s birthday party in his house. "Do you mind if I borrow Bella for the evening?" (2006:12). Edward masculinity impacts the woman remarks against him during his life. Edward is very masculine, handsome and charming like a prince obviously attract a lot of eyes to adore him. Edward character is very charming, beautiful face and good manners make him become the idol of many women during his lifetime. Many woman who want to be his spouse, including Bella. Everything’s on Edward make Bella fall in love him unconditionally, irrevocably, even willing to die for him. So many women who admire Edward, but Edward just choose Bella who is finally become a vampire like him. “You can have my soul. I don’t want it without you—it’s yours already!" (2006:37). Edward’s charming isn’t only appear in his physicly appearance, but also in his personality. Edward masculinity affect to his personality in being wise. Being rational is being reasonable and being analytical is having ability to solve problem. In short, being rational and analytical is being wise. Being rational and analytical make Edward have a firm stance on what to believe. Edward is not easy to accept the opinions or stories from other people that he does not find the truth by his own. Edward would figure out by himself or ask the person concerned to ascertain the truth. His ability to analyze something also makes him able to read Bella’s mind little bit. Bella is the only one exception in Edward’s mind-reading abilities, but with Edward analytical skills, he was able to read a bit of what Bella will do then. Like when Alice saw Bella jumping off a cliff, Edward received the news of Rosalie, but Edward does not necessarily believe in the news. Edward tried to call Bella’s home to ask what was going on. The other of Edward analyzing is to hide his property with Bella, to avoid Bella will remember later. Edward understood that this will not be able to make Bella forget him. Edward Cullen’s masculinity impact in his life made him become a man that is strong and charismatic. His strong feature made him become a strong individual man that is dominant. His domination caused he become over protective and intelligent. Edward Cullen’s charismatic feature formed him become a wise man that is good looks and behave. Edward’s behave isn’t only in his appearance but also in personality. CONCLUSION Based on the analysis of the previous chapter, the main character of Stephenie Meyer’s New Moon, Edward Cullen is a masculine man. Family role become the base of Edward Cullen’s characteristics that is shown in his personality. Then his characters become his background to live in his social life. So, everything he does based on his masculine characteristics put impacts to his life. Edward Cullen lived in the family in the middle of war time, well educated by his parents. The divided of family role by his parents, make Edward Cullen has well family background that could make him become masculine man. Well educated by his family, Edward Cullen has masculine characteristics such as dominant, brave, rational, intelligent, analytical, aggressive, and independent. Masculine characteristics of Edward Cullen lead him become gentlemen in his social life. Edward Cullen has good manner in dressed and behavior. Great family role education, masculine characteristics, and good manner are Edward Cullen masculinity verification. Everything always comes followed by its impact. So does Edward Cullen. Edward Cullen’s masculinity also has impacts to his life. All of those masculine characteristics of Edward Cullen have affect to his life very well. With all those characteristics Edward Cullen becomes a figure of man that is strong individual and charismatic. Edward Cullen strong individual character made him become strong person that is dominant and smart. Edward Cullen’s strong individual pushed him become smart because he has to have good reason in everything he decided. Strong individual also means that he bravery taking risk in his decision. Become charismatic man support by Edward Cullen’s wise characteristics which are rational and analytical. Because of charismatic isn’t always inner characteristic but also in appearance, Edward Cullen is charming man that is have good looks and behave. So, Edward Cullen is a masculine man that is formed by his family role that made him become that masculine in his social life. And his masculine characteristics have impacts to his life such as strong individual and charismatic. REFERENCES Bernstein, J.M. 1984. The Philosophy of the Novel: Lukacs, Marxism and the Dialectics of Form. Minneapolis: University of Minnesota Press. Brannon, Linda. 1976. Gender: Psychological Perspective. Massachusetts: Allyn and Bacon. Connell, R.W. 1995. Masculinities. Berkeley: University of California Press. Esplen, Emily and Jolly, Susie. 2006. Gender and Sex, Sussex: University of Sussex Press. Halberstm, Judith. 1998. Female Masculinity. London: Duke University Press. Lehman, Peter. 2001. Masculinity: Bodies, Movies, Culture, Ed. New York: Rouledge. Macionis, John. 1991. Sociology, Third Edition. New Jersey: Prentince-Hall, Inc. Malti-Douglas, Fedwa. 2007. Encyclopedia of Sex and Gender, New York: Macmillan Company. Peck, John and Coyle, Martin. 1988. “Novel” Literary Terms and Criticism. London:Macmillan. Perrine, Laurence. 1959. Story and Structure. New York: Harcourt Brace and World,Inc. Schafer, Richard T. and Lamm, Robert P. 1992. Sociology, Fourth Edition. New York: McGraw-Hill, Inc